Molecular interaction between Ganoderma boninense and young oil palm - Supramaniam, Christina Vimala (2016)
Oil palm is an important crop to the economy of Malaysia and Indonesia. There have been considerable efforts to improve crop quality of crop to meet the growing demands for edible oil in the world. However, the threat of pests and diseases in Malaysian oil palm has increasingly challenged the production of crude palm oil, sometimes to the point of driving plantations to closure and conversion of estate land for commercial development. The most devastating disease in oil palm is basal stem rot (BSR), caused by the root-rot pathogen Ganoderma boninense. The disease has been observed in both young and mature oil palm and in both inland and coastal plantations. Epidemiology of BSR was explained through infection by spores and by mycelium from previously infected oil palm and coconut stands, and the presence of G. boninense in the basal stem and soil surrounding infected palms. The life cycle of G. boninense could extend to years as the fungus can remain as resting structures in palm tissues and as recalcitrant spores spread by wind and rain splash in estates. Shade house trials have been successful in producing artificially infected Ganoderma-oil palm BSR symptoms. However, the current method uses oil palm seedlings of three to 12 months and involves inoculation with G. boninense that has pre-colonised a rubber wood block for one month. This method requires a minimum of six months to observe BSR-like symptoms, a time consuming effort. The aim of this work was to develop an efficient artificial infection assay that uses clonal oil palm plantlets as hosts for BSR disease through the inoculation of G. boninense isolate GBLS. The experiment was set up with treatments of T1: non-treatment control, T2: wounded plant control and T3: wounded and GBLS-infected plants. During the incubation period of 42 days, T3 plants consistently showed significant stunting (5.18% and 13.41% shorter than T1 and T2, respectively) and loss of weight (57.58% and 61.00% lighter than T1 and T2, respectively). The T3 plants also had significantly thinner leaves (38.70% and 37.71% narrower than T1 and T2, respectively) and lower chlorophyll contents (42.95% and 64.88% lower SPAD readings than T1 and T2, respectively). Disease severity on the T3 plants was 100% by 6 weeks, indicating death of oil palms. The quantity of GBLS DNA present in T3 samples was highest at Day 14, corresponding to the active growth phase of the pathogen, while on Day 42, the quantity of DNA increased to 13.58% of Day 14 readings, indicating continuous growth in vivo. The method developed was time-sensitive and reliable for screening oil palm for response during the plant-pathogen interaction. The work examined the hypothesis that G. boninense utilizes lignin degrading enzymes (LDEs) such as laccase, lignin peroxidase (LiP) and manganese-dependent peroxidase (MnP) to breakdown oil palm lignin, causing primary cell, tissue and stem rot. Therefore, the role of laccase was investigated during the interaction in otherwise symptomless oil palm tissues. A small gene fragment (208 bp) of laccase was isolated from total DNA of G. boninense GBLS and sequencing showed it to contain 89% homology to basidiomycete laccase. GBLS reduced the total lignin content of oil palm in T3 plants (48.86% and 53.18% lower than T1 and T2, respectively). However, neither laccase nor MnP enzymes were produced in significantly higher amounts in T3 as compared to T1 and T2, indicating the need to differentiate the presence of plant and fungal laccases. Transcript abundance for GBLS laccase gene using qPCR indicated that laccase was induced during the interaction, with maximum laccase detected on Day 28. However, this did not place laccase as a virulence factor although the presence of higher amounts of laccase towards the end of the experiment corresponds to loss of lignin and plant death. Therefore, laccase and other LDEs need further investigations to be confirmed as virulence factors.